ALGUNOS FACTORES ECOLOGICOS QUE INFLUENCIAN LA DISTRIBUCION ESPACIAL DE NIDOS DE HORMIGAS - Covarrubias, R.; Fueyo, R.; Ipinza, J. (Acta Entomológica Chilena, 2022)
The ant community is quantitatively studied along an altitudinal gradient, between 1640 and 3060 m (Andes Cordillera, Baños del Flaco, Chile). By means of correlation tests, associations are obtained between the following ecological factors: altitude, plant cover, stone cover, soil texture, pH and the number of ant species or the number of ant nests. The altitudinal distributions of all above mentioned factors are analyzed in detail. The minimal areas of the ant community corresponding to three quadrants were determined for each sampled altitude. For the different quadrants, the dimensión of the minimal area is found to be posilively correlated with the number of species.